Evaluation of marginal misfit of implant-supported fixed prostheses made using different techniques - Gomes, Jéssica Marcela de Luna [UNESP]; de Moraes, Sandra Lúcia Dantas; Júnior, Joel Ferreira Santiago; Lemos, Cleidiel Aparecido Araujo [UNESP]; Grossi, Márcio Lima; Pellizzer, Eduardo Piza (Quintessence Publishing, 2019)
Purpose: To evaluate the vertical marginal (VM) and horizontal marginal (HM) misfit of frameworks made using different techniques. Materials and Methods: A total of 30 frameworks were divided into three groups of 10 samples each based on manufacturing technique: nichrome cast (G1), milled in zirconia (G2), and milled in wax and fused to metal (G3). Marginal misfit was measured using a three-dimensional optical microscope. Results: The highest VM misfit was in G3 (83.5 μm), followed by G1 (55 μm) and G2 (42 μm). The highest HM misfit was in G2 (118 μm), followed by G3 (102 μm) and G1 (-85 μm). Conclusion: Frameworks milled in zirconia resulted in the lowest VM misfit, while frameworks filled in wax and fused to metal resulted in higher VM. The HM misfit was favorable in the lost-wax technique.